Crohn's disease presenting as multiple pulmonary nodules in FDG PET/CT scan - Mevlüt Kurt,; Emrah Poşul,; Güray Can,; Bülent Yılmaz,; Uğur Korkmaz,; Özlem Kar Kurt,; Kamil Gürel,; Emine Dağıstan,; Gülzade Özyalvaçlı, (Turkish Journal of Gastroenterology, 2019)
-